Análisis comparativo del nivel de pobreza y extrema pobreza en la zona norte, región Ancash, caso: Corpanqui y Ticllos - Ramírez Miranda, Ridberth (2009)
In this study we consider the research from an empirical delineation of the Ancash region, the most remote and inaccessible, in which the difficulties of both the location and traffic are a major obstacle in the fight against poverty, so the research area are objective and leads to qualitative research, so that led us to know the real situation of poverty and extreme poverty in Corpanqui and Ticllos.